How persistent are duplication of purchase partitions?. Issue 1 (4th September 2021) - Anesbury, Zachary William; Bennett, Dag; Kennedy, Rachel
Abstract: Brands share more of their customers with bigger competitors and fewer with smaller ones. However, there are occasional deviations to this predictable Duplication of Purchase (DoP) pattern. When two or more brands share excess customers because of functional or nonfunctional differences—it is called a partition. While past research using the NBD‐Dirichlet model demonstrates partitions in annual or shorter data, there is no empirical evidence for partition persistency over the longer term, although some other NBD‐Dirichlet deviations are known to persist over time. Examining expected partitions in 10 consumer goods categories in the United Kingdom, the authors show partitions overwhelmingly persist over 3 years. The findings contribute support to Dirichlet theory, especially on market stability, boundary conditions, and provide practical implications for portfolio management.